Ruthenium(II)‐Catalyzed Double Annulation of Quinones: Step‐Economical Access to Valuable Bioactive Compounds. Issue 48 (9th July 2020) - da Silva Júnior, Eufrânio N.; de Carvalho, Renato L.; Almeida, Renata G.; Rosa, Luisa G.; Fantuzzi, Felipe; Rogge, Torben; Costa, Pedro M. S.; Pessoa, Claudia; Jacob, Claus; Ackermann, Lutz
Abstract: Double ruthenium(II)‐catalyzed alkyne annulations of quinones were accomplished. Thus, a strategy is reported that provides step‐economical access to valuable quinones with a wide range of applications. C−H/N−H activations for alkyne annulations of naphthoquinones provided challenging polycyclic quinoidal compounds by forming four new bonds in one step. The singular power of the thus‐obtained compounds was reflected by their antileukemic activity. Abstract : Ruthenium(II)‐catalyzed C−H/N−H double annulation reactions were realized for the formation of polycyclic quinones enabling the assembly of antitumor compounds.